2014
DOI: 10.31018/jans.v6i2.507
|View full text |Cite
|
Sign up to set email alerts
|

Heterosis, dominance estimate and genetic control of yield and post harvest quality traits of tomato

Abstract: Paucity of research on the development of tomato hybrid having desirable post harvest/or processing quality in the tropics compel to undertake this study. Therefore, the present investigation was undertaken to identify potential donors and crosses, to study the extent of heterosis and dominance behaviour, and to ascertain the genetic control of fifteen yield components and post harvest quality traits through line x tester mating design in tomato. Non-additive gene action controlled all characters studied, sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 7 publications
2
11
1
Order By: Relevance
“…The equal importance of both additive and non-additive gene actions for the control of polar diameter of fruit (Hazra and Nath, 2008), equatorial diameter of fruit and locules fruit -1 (Mondal et al, 2009) have also been documented. On the contrary to the present findings, previous workers also noted the importance of non-additive genetic effects for locules fruit -1 (Chattopadhyay et al, 2011;Sherpa et al, 2014), and additive gene effect for PDI of ToLCV disease (Farzane et al, 2012). The genetic constitution of the donor parents, environmental variation, crossing techniques used in analyzing the data and the precision of the experiment might play some important role for such disparities from previous results.…”
Section: Resultscontrasting
confidence: 99%
See 4 more Smart Citations
“…The equal importance of both additive and non-additive gene actions for the control of polar diameter of fruit (Hazra and Nath, 2008), equatorial diameter of fruit and locules fruit -1 (Mondal et al, 2009) have also been documented. On the contrary to the present findings, previous workers also noted the importance of non-additive genetic effects for locules fruit -1 (Chattopadhyay et al, 2011;Sherpa et al, 2014), and additive gene effect for PDI of ToLCV disease (Farzane et al, 2012). The genetic constitution of the donor parents, environmental variation, crossing techniques used in analyzing the data and the precision of the experiment might play some important role for such disparities from previous results.…”
Section: Resultscontrasting
confidence: 99%
“…The highest per se performance for fruit yield plant -1 along with fruit weight, polar diameter, equatorial diameter, pericarp thickness and TSS content of fruit was recorded in CLN 2777E followed by CLN 2777F. Significant and positive gca effects for fruit weight (Farzane et al, 2012) and fruit yield plant -1 (Izge and Garba, 2012;Sherpa et al, 2014) have also been reported. Considering per se performance and gca effects, two parents namely, CLN 2777F and CLN 2777E could be identified as good donor parents for improvement of fruit yield having better processing quality traits and tolerance to leaf curl virus in future breeding programme.…”
Section: Resultsmentioning
confidence: 90%
See 3 more Smart Citations